Penambahan Berat Badan Ibu Hamil Terhadap Berat Bayi Lahir Di Kota Mataram - Deviana Oktadianingsih; Irianto Irianto; AASP Chandradewi; IKetut Swirya Jaya (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Low Birth Weight (LBW) is an indicator of mother and children health. The LBW in Mataram City has increased from 3,11% in 2013 to 3,38% in 2014. One of the cause of LBW is pregnancy weight gain. Objective : To know the pregnancy weight gain with birth weight. Research Methods. This research used cross-sectional design. The population is mother who have done childbirth in the working area of Puskesmas in Mataram City in 2016. The research sample is 78 mother, 39 mothers at LBW and 39 mothers at Non LBW by Systematic Random Sampling techniq. The Multiple regression is the mehod to analyzed pregnancy weight gain with birth weight. Research Result. The pregnancy weight gain and the other ekstrinsik factors has an association with birth weight (p<0,05). The other ekstrinsik factor are significantly related to birth weight is ANC, the morbidities during pregnancy and Hb. Conclusion. Some consider the weight of pregnant women and other extrinsic factors (ANC visits, comorbidities, and Hb levels) to the weight of the baby born.